Gene Repositioning Is Under Constraints After Evolutionary Conserved Gene Neighborhood Separate - Dai, Zhiming (Frontiers in Genetics, 2019)
Genes are not randomly distributed on eukaryotic chromosomes. Some neighboring genes show order conservation among species, while some neighboring genes separate during evolution even though their neighborhood is conserved among some species. Here, I investigated whether after-separation gene repositioning are under natural selection for evolutionary conserved gene neighborhood compared with non-conserved neighborhood. Genes with conserved neighborhood show low expression divergence after separation. After genes separate from their conserved gene neighbors, I found that specific genes showing co-expression and co-protein-complex with their before-separation gene neighbors tend to be selected as their after-separation gene neighbors. These results demonstrate evolutionary constraints on the selection of neighboring genes after evolutionary conserved gene neighborhood separate.